2001
DOI: 10.1176/appi.ps.52.4.508
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Behaviors and Their Relationship to Posttraumatic Stress Disorder Among Women Prisoners

Abstract: HIV risk behaviors before incarceration were highly prevalent among the women in this study. Rates of PTSD, depression, and dysthymic disorder were also high. PTSD was associated with prostitution and receptive anal sex, and the disorder may contribute to high rates of risky sexual behavior. Targeted HIV risk reduction efforts among women prisoners should include evaluation for PTSD; conversely, women prisoners with a diagnosis of PTSD should be evaluated for prior HIV sexual risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 41 publications
6
78
3
1
Order By: Relevance
“…35,[37][38][39] Four identified studies addressed HIV risk taking in the context of substance abuse in subjects within the CJS (Table 3). 37,[40][41][42] These studies all confirm that HIV risk is heightened in the setting of concurrent violence. Furthermore, among women within the CJS, victimization and sexual risk taking appear to be moderated by contextual factors, such as substance abuse and relationship to one's sexual partner.…”
Section: Subjects Within Criminal Justice Systemmentioning
confidence: 66%
“…35,[37][38][39] Four identified studies addressed HIV risk taking in the context of substance abuse in subjects within the CJS (Table 3). 37,[40][41][42] These studies all confirm that HIV risk is heightened in the setting of concurrent violence. Furthermore, among women within the CJS, victimization and sexual risk taking appear to be moderated by contextual factors, such as substance abuse and relationship to one's sexual partner.…”
Section: Subjects Within Criminal Justice Systemmentioning
confidence: 66%
“…While research has shown Post-Traumatic Stress Disorder (PTSD) to be common among female detainees, 8,[23][24][25] this study failed to ascertain the prevalence of PTSD among participants. Questions regarding sensitive topics such as drug use and sexual risk behavior relied on self-report and may have elicited socially desirable responses.…”
Section: Release From Jail: Moment Of Crisis or Window Of Opportunitymentioning
confidence: 83%
“…Furthermore, some programs focus on known proximal determinants of high-risk sexual behavior that are psychosocial in nature, such as communication, perceived risk, and intention to use condoms (Grossman et al, 2008;Noar, Carlyle, & Cole, 2006). Currently, programs aimed at uniformed personnel do not directly address psychopathology in prevention efforts, despite elevated rates of major depressive disorder (MDD) and posttraumatic stress disorder (PTSD) among soldiers (Gahm & Lucenko, 2008)-disorders that have been associated with sexual risk behavior in nonmilitary populations (Hutton et al, 2001;Hutton, Lyketsos, Zenilman, Thompson, & Erbelding, 2004).…”
mentioning
confidence: 99%